Access to anticancer medicines in public hospitals of Northwestern China - Ma, Yue; Peng, Jin; Yao, Xuelin; Feng, Liuxin; Shi, Xinke; Jiang, Minghuan (Frontiers in Public Health, 2023)
Objective: With the increasing incidence and mortality of cancer, we aimed to evaluate the accessibility of anticancer medicines in public hospitals of Shaanxi, a representative province of Northwestern China. Methods: Thirty-one anticancer medicines were investigated in 146 designated public hospitals in 10 cities of Shaanxi Province. We used medicine procurement data from the Shaanxi Drug Centralized Purchasing Platform during 2019–2021. Primary outcomes included the availability, drug utilization, and affordability of anticancer medicines. Results: The mean availability of 31 anticancer medicines increased significantly from 5.45% in 2019 to 14.72% in 2021. The mean availability of nationally negotiated medicines was significantly lower than that of Class B medicines (8.72% versus 12.85%, P=0.048). The mean availability of injectable medicines was significantly greater than that of oral medicines (13.66% versus 8.77%, P=0.007). In 2019–2021, the annual mean amount purchased increased significantly from CNY 6.51 million to CNY 18.56 million (P=0.007). The mean defined daily doses (DDDs) of 31 medicines significantly rose from 225.50 to 1019.50 (P=0.008) whereas their annual mean defined daily drug cost (DDDc) significantly decreased from CNY 551.15 to CNY 404.50 (P<0.001). The DDDs of anticancer medicines were associated with different regions and medicine catalogs whereas the DDDc was associated with medicine catalogs and dosage forms. The percentage of catastrophic health expenditure decreased from 71.0% to 51.65% and from 90.30% to 80.60% for urban and rural residents, respectively. The affordability of nationally negotiated medicines was significantly lower than that of Class B medicines (P=0.032), and the affordability of injectable medicines had no significant difference compared to that of oral medicines (P=0.124) for both urban and rural residents. Conclusion: The accessibility of anticancer medicines improved dramatically in public hospitals of Northwestern China during the period 2019–2021.